Worst–case latency of broadcast in intermittently connected networks. (14th November 2012) - Asplund, Mikael; Nadjm–Tehrani, Simin
Worst–case latency is an important characteristic of information dissemination protocols. However, in sparse mobile ad hoc networks where end–to–end connectivity cannot be achieved and store–carry–forward algorithms are needed, such worst–case analyses have not been possible to perform on real mobility traces due to lack of suitable models. We propose a new metric called delay expansion that reflects connectivity and reachability properties of intermittently connected networks. Using the delay expansion, we show how bounds on worst–case latency can be derived for a general class of broadcast protocols and a wide range of real mobility patterns. The paper includes theoretical results that show how worst–case latency can be related with delay expansion for a given mobility scenario, as well as simulations to validate the theoretical model.